Effects of the Vita Slim and Green Tea as Anti-obesity Drugs on Certain Biochemical and Physiological Indices of Obese Adult Male Albino Rats - Eman G. E. Helal; Nora A. Aljalaud; Ashraf M. M. Algendy; Suzan S. Elpasty (Recent Developments in Chemistry and Biochemistry Research Vol. 8, 2024)
Background: A larger number and larger size of fat cells characterize obesity, a condition that has a detrimental effect on one’s health. Because obesity is linked to an increased risk of diabetes and heart disease, the ideal anti-obesity medication would have weight loss that was long-lasting and had few side effects. Objective: The objective of the study is to detect if the weight-loss drugs; green tea and Vita Slim negatively affect several biochemical and physiological markers. Materials and Methods: This study utilized a total of twenty-one albino male rats (220±20 g). Rats were purchased from an animal unit of the Nile Pharmaceutical Company, Cairo, Egypt. Three groups consisted of 21 mature obese male albino rats (with a body weight of 220 ±20 gram): In Group one: control (vehicle treatment), in group two: for a period of 30 days, rats were given Vita slim (0.1mg/kg/day), and in group three: for 30 days, rats were given green tea (0.1 mg/kg/day). Results: Significant changes were observed in the weight of the treated groups, in serum levels of AST/ALT, albumin, triglycerides, low-density lipoproteins (LDL), LDL/HDL ratio, urea, creatinine, as well as triiodothyronine (T3) as compared with the control group. It is proven that thyroid hormones, particularly T3, are important metabolic hormones. Energy generation is linked to the quantity of thyroid hormones in the bloodstream. Conclusion: The study concluded that Vita Slim and green tea capsules have a deleterious influence on critical biochemical and physiological markers, notably liver functions. Several physiological and biochemical markers, including kidney and liver functions, have been shown to be negatively impacted by Vita Slim and green tea after 30 days of ingestion.